Community interpreting in Sweden and its significance to guaranteeing legal and medical security - Norström, Eva (Sens public)

(untitled) (Département des littératures de langue française, 2010)
In this presentation, I deal with the legal situation in Sweden concerning the right to interpretation. I discuss the philosophy behind the right to interpretation given to public servants, medical staff as well as immigrants and minorities in Sweden. I also deal with the question of who the ideal interpreter is. What kind of education is offered and what skills are fundamental to master? What further skills are required, besides language and factual knowledge, in order to maintain legal and medical security? What are the codes of ethics? Furthermore, I compare this with the reality of the interpreter. What is his or her legal status and working conditions? Finally, I discuss who is responsible for guaranteeing legal and medical rights and why access to professional interpreting in the public sector is a concern of the state.